U-Pb, Lu-Hf, and trace element zircon data from plutonic rocks of the New England Avalon terrane, USA - Kuiper, Yvette D.; Murray, Daniel P.; Crowley, James L. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
New zircon U–Pb, Lu–Hf and trace element laser ablation inductively coupled mass spectrometry (LA-ICP-MS) data are presented for ten Ediacaran granitoid samples from the New England Avalon terrane, and from possibly exotic blocks of southeastern Massachusetts and Rhode Island, USA. Crystallization ages of the analyzed samples are ca. 611–577 Ma, with nine samples between ca. 611 Ma and ca. 588 Ma. These overlap with previously published ca. 620–589 Ma ages of granitoid rocks and ca. 597–584 Ma ages of volcanic complexes in the northern part of the terrane, where volcanism occurred immediately after plutonism. A granite that cuts sedimentary and volcanic rocks with a previously determined maximum depositional age of ca. 613 Ma in southern Rhode Island yielded a zircon chemical abrasion isotope dilution thermal ionization mass spectrometry (CA-TIMS) date of 609.30 ± 0.22 Ma. Volcanism therefore occurred between ca. 613 Ma and ca. 609 Ma, and ca. 10 myr prior to that in the northern part of the New England Avalon terrane. This area may be part of the previously interpreted exotic Newport Block.Zircon εHf(t) values of all samples are -2.8–6.0, with ca. 1.23–0.96 Ga TDM1 Hf model ages. These values are also consistent with published εHf(t) values between -3.1 and 5.9 of nine published plutonic and volcanic rocks. Zircon trace element geochemistry data show mostly mixed continental arc and oceanic island signatures. The Eu/Eu* values are mostly 0.1–0.7, suggesting ~30–80 km crustal thicknesses. The exception is a sample southeast of the Nauset magnetic anomaly on the southeastern tip of Massachusetts, which has the highest zircon ∑REE values, mostly Nb/Hf >0.001, generally low Eu/Eu* values, and high εHf(t) values, all suggestive of a within-plate/anorogenic/rift setting. The new data provide a valuable reference data set, guiding future studies on the New England Avalon terrane and/or adjacent exotic blocks and on similar crustal domains elsewhere.